Leadership and Human Resource Management in Project Circumstances - Fadjar, Adnan (SMARTek, 2008)
Leadership is a very important issue in any organizations. The complexity of a project makes the role of the project manager as the leader even more challenging because he/she has to work in an organization which has relatively short time period and dealing with many people who come from various backgrounds. This paper discusses various theories of leadership and proposes their application in project circumstances. As It is often said that the project management is effective if it can manage the conflicts that occur within the project’s life span, this paper also suggests approaches for managing conflicts in project circumstances.